2021
DOI: 10.20870/oeno-one.2021.55.1.4558
|View full text |Cite
|
Sign up to set email alerts
|

Reducing SO<sub>2</sub> content in wine by combining High Pressure and glutathione addition

Abstract: The aim of this work was to examine the potential of High Pressure (HP) technology as an alternative technique to SO2 addition for red wine preservation. It focused on producing wines with reduced added SO2 and the simultaneous addition of glutathione (GSH) as a natural antioxidant. Selected quality parameters of red wine samples from Mouchtaro grapes treated by HP using various pressure parameters were tested. HP processing studied was applied at 200, 400 and 600 MPa for 0, 5 and 15 min. The application of HP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 75 publications
0
1
0
Order By: Relevance
“…Although the use of SO 2 for the conservation of wines is an old practice (Gould and Russell, 2003), ingestion of sulphites through the consumption of food and drink can cause some related adverse clinical effects (Vally et al, 2009) ; for this reason, there is a worldwide movement towards decreasing the concentration of sulphites in wines. Although several studies have shown alternatives for SO 2 and sought to reduce its use (Capece et al, 2020;Christofi et al, 2021;Marchante et al, 2019;Shih et al, 2020;Simonin et al, 2020;Zara and Nardi, 2021), to date, no other physical technique or chemical additive can provide the efficacy and broad spectrum of action of this compound (Lisanti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Although the use of SO 2 for the conservation of wines is an old practice (Gould and Russell, 2003), ingestion of sulphites through the consumption of food and drink can cause some related adverse clinical effects (Vally et al, 2009) ; for this reason, there is a worldwide movement towards decreasing the concentration of sulphites in wines. Although several studies have shown alternatives for SO 2 and sought to reduce its use (Capece et al, 2020;Christofi et al, 2021;Marchante et al, 2019;Shih et al, 2020;Simonin et al, 2020;Zara and Nardi, 2021), to date, no other physical technique or chemical additive can provide the efficacy and broad spectrum of action of this compound (Lisanti et al, 2019).…”
Section: Introductionmentioning
confidence: 99%